Association between visceral fat area and diabetic retinopathy among people with type 2 diabetes mellitus: a cross-sectional study in Ningbo, Zhejiang Province, China - Hua, Shanshan; Yao, Dongwei; Wu, Siteng; Chen, Miao; Li, Li; Li, Bo (Frontiers in Medicine, 2024)
The objective of this study is to investigate the relationship between visceral fat area (VFA) and diabetic retinopathy (DR) in the context of type 2 diabetes mellitus (T2DM) within Ningbo, China. Methods: The data of a total of 3,707 subjects with T2DM treated at The First Affiliated Hospital of Ningbo University were enrolled. The existence and severity of diabetic retinopathy were assessed by employing the 45°22 two-field stereoscopic digital photography. Subjects were categorized into four distinct groups: those without DR (NDR), individuals with mild non-proliferative DR (mild NPDR), people with moderate non-proliferative DR (moderate NPDR), and those suffering from vision-threatening DR (VTDR). Bio-electrical impedance was employed to estimate the Visceral fat area (VFA). Multinomial logistic regression models were utilized to evaluate the association between VFA and DR. Results: The mean VFA in patients without diabetic retinopathy (NDR) was notably lower compared to that of patients with diabetic retinopathy (DR) (85.21 ± 37.78 vs. 97.37 ± 44.58 cm 2 , P < 0.001). As the severity of DR increased, VFA increased gradually but insignificantly (94.41 ± 43.13 cm 2 , 96.75 ± 40.82 cm 2 , 100.84 ± 49.34cm 2 , p = 0.294). After adjusting the confounding factors, there was an association identified between VFA and the occurrence of DR (OR = 1.020, 95% CI = 1.016-1.024). It showed that regardless of BMI, whether it's less than 25 kg/m 2 or greater than or equal to 25 kg/m 2 , a higher VFA (≥ 100cm 2 ) level came with a higher prevalence of DR (P < 0.001).The outcomes of this research indicate a modest association between VFA and the incidence of DR among Chinese patients who have been diagnosed with T2DM in Ningbo.